Tafsir bi al-Ray dan Manhaj Tarjih al-Tabari dalam Tafsir - Said, Khairuddin; Hj Mohd Yusuf, Zulkifli (Jurnal Usuluddin, 2005)
The exegesis of the Quran entitled Tafsir al-Tabari has been acknowledged as the main references of all of the exegeses of the Quran that comes after it. Tafsir al-Tabari has been classified as the exegesis of the Quran from the bi-al-Mathur (based on narrations) understanding where major part of its contents have been represented by the narrations. However, al-Tabari also uses opinion (in making the exegeses of the Quran) while choosing the best decision from the mentioned narrations. This article is going to analyse few exegeses of the Quran that has been based on opinion which have been done by al-Tabari focusing on al-Isra verses.